The Role of School Supervisors in Supporting the Flagship Character Education Development Program at Elementary School - Tulus Bintoro; Nur Khoiri; Widya Kusumaningsih (Journal of Innovation and Research in Primary Education, 2026)
This study examined the role of school supervisors in assisting the implementation of the flagship character education development program at SD Negeri 1 Depok, Grobogan Regency, during the 2025/2026 academic year. Despite growing recognition of supervisory functions in school quality improvement, empirical evidence on how supervisors operate within structured, government-mandated character education programs at the elementary level remains limited. This study employed a qualitative case study design. Data were collected through semi-structured interviews, classroom observations, and document analysis involving five participants — one school supervisor, one principal, and three teachers — and analyzed using Miles et al.'s (2014) interactive model. Four themes emerged: systematic program planning, collaborative supervisory assistance, structured follow-up actions, and positive impact on students' character development. An unexpected finding was the emergence of peer-to-peer character reinforcement among students, suggesting that sustained supervisory engagement may facilitate value internalization beyond the teacher–student dyad. These findings demonstrate that supervisory assistance, when conducted collaboratively and continuously, constitutes a transformative institutional mechanism for character education. The study contributes to educational supervision scholarship and offers practical guidance for supervisors and policymakers in strengthening elementary character education programs.